Reality Group Counseling with WDEP and Art Therapy to Enhance Resilience in Orphanage Adolescents - Nadia Khairunnisa; Muhammad Nur Wangid; Azahra Hardi Cusinia (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Adolescents in orphanages face psychosocial challenges, including emotional deprivation and limited family support, that hinder resilience development. This study examines the effectiveness of reality group counseling using the WDEP technique combined with art therapy in improving the resilience of orphanage adolescents. A quasi-experimental design with a non-equivalent control group was employed, involving 14 adolescents from Panti Asuhan Miftahunnajah (7 experimental, 7 control) selected through purposive sampling. The Connor-Davidson Resilience Scale (CD-RISC, α = 0.885) was used for measurement. The experimental group received six sessions of WDEP-based reality group counseling integrated with art therapy. Results showed a significant improvement in the experimental group (p = 0.018, Wilcoxon Signed Rank Test), with an average N-Gain of 0.7654 (76.54%), classified as high effectiveness. The control group showed no significant change (p = 0.611). These findings confirm that integrating WDEP and art therapy within group counseling is an effective and comprehensive approach to strengthen resilience among orphanage adolescents. Keywords: reality group counseling, WDEP technique, art therapy, resilience, orphanage adolescents